Saikosaponin A modulates remodeling of Kv4.2-mediated A-type voltage-gated potassium currents in rat chronic temporal lobe epilepsy - Hong Y; Deng N; Jin H; Xuan Z; Qian YX; Wu ZY; Xie W (Dove Medical Press, 2018)
Yu Hong,1,2,* Ning Deng,1,* Han-Na Jin,3 Zheng-Zheng Xuan,4 Yi-Xiao Qian,1 Zhi-yong Wu,1,2 Wei Xie1,2 1Department of Traditional Chinese Medicine, School of Traditional Chinese Medicine, Southern Medical University, Guangzhou, China; 2Department of Traditional Chinese Medicine, Nanfang Hospital, Southern Medical University, Guangzhou, China; 3Department of Internal Neurology, People’s Hospital of Huizhou Zhongkai Hi-tech Industrial Development Zone, Huizhou, China; 4Neuroelectrophysiological Examination Room, Traditional Chinese Medicine Hospital of Guangdong Province, Guangzhou, China *These authors contributed equally to this work Background: Chronic temporal lobe epilepsy (cTLE) is the most common intractable epilepsy. Recent studies have shown that saikosaponin A (SSa) could inhibit epileptiform discharges induced by 4 action potentials and selectively increase the transient inactivating K+ currents (IA). However, the mechanisms of SSa on IA remain unclear. In this study, we comprehensively evaluated the anticonvulsant activities of SSa and explored whether or not it plays an anti-epileptic role in a Li-pilocarpine induced epilepsy rat model via remodeling Kv4.2-mediated A-type voltage-gated potassium currents (Kv4.2-mediated IA).Materials and methods: All in vitro spontaneous recurrent seizures (SRS) were recorded with continuous video monitoring. Nissl’s staining was used to evaluate the SSa protection of neurons and immunohistochemistry, Western blot, and quantitative reverse transcription PCR were used to quantify the expression of Kchip1 and Kv4.2 in the hippocampal CA1 field and the adjacent cortex following Li-pilocarpine induced status epilepticus. We used whole-cell current-clamp recordings to evaluate the anticonvulsant activities of SSa in a hippocampal neuronal culture model of cTLE, while whole-cell voltage-clamp recordings were used to evaluate the modulatory effects of SSa on Kv4.2-mediated IA.Results: SSa treatment significantly reduced the frequency and duration of SRS over the course of eight weeks and increased the production of Kchip1 and Kv4.2. In addition, SSa attenuated spontaneous recurrent epileptiform discharges (SREDs) in the hippocampal neuronal model and up-regulated Kv4.2-mediated IA.Conclusions: SSa exerted a disease-modifying effect in our cTLE rat model both in vivo and in vitro; the increase in Kv4.2-mediated IA may contribute to the anticonvulsant mechanisms of SSa. Keywords: saikosaponin A, epilepsy, pilocarpine, Mg2+-free, Kchip1, Kv4.2-mediated IA